Implementation of Halal Tourism in Lombok Island (Study on the Compliance of Tourism Actors with the Halal Tourism Regulation) - Rahmatullah (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The tourist business of Lombok, particularly the Muslim-friendly sector, was severely impacted by the declaration of COVID-19 as a worldwide pandemic in March 2020. The difficulty that still exists at the present day is the application of the policies mandated by law. One of the criteria for the establishment of halal tourism in line with Regional Regulation No. 2 of 2006 is whether or not the process has been carried out correctly and is supported by government monitoring. According to Soerjono Soekanto's theory of legal efficacy, this study employs a sociological or empirical legal research technique (sociology of law). A community's response to a law provides insight into the effectiveness of the law. In order for a law or legislation to be successful, it must result in changes in behavior on the part of the community members that bring about the intended outcome.